PENGARUH CORPORATE GOVERNANCE TERHADAP HUBUNGAN BESARAN DAN PENGUNGKAPAN TRANSAKSI PIHAK BERELASI DENGAN MANAJEMEN LABA: STUDI EMPIRIS PERUBAHAN PSAK NO. 7 - Juvita, Desriana; Siregar, Sylvia Veronica (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2013)
The purpose of this research is to examine the effects of effectivity of board of commisionerand audit committee on the relationship between related party transactions (RPT) amountand disclosure on earnings management. This research is using 86 samples of the company inmanufacturng industry on 2010 and 2011 to see the comparation of the changes in PSAK No.7.The result shows board of commisioner and audit committee effectiveness weaken the relationshipbetween amount of RPT and earnings management. Moreover, disclosure of RPT according toPSAK No.7 (revised 2010) and Bapepam-LK weaken the relationship between RPT and earningsmanagement.